Modifications of intravitreal injections in response to the COVID-19 pandemic. Issue 9 (20th July 2021) - Weng, Chang-Chi; Lin, Ting-Yi; Yang, Yi-Ping; Hsiao, Yu-Jer; Lin, Tzu-Wei; Lai, Wei-Yi; Lin, Yi-Ying; Chou, Yu-Bai; Lin, Tai-Chi; Chiou, Shih-Hwa; Hwang, De-Kuang; Chen, Shih-Jen
Abstract : The Coronavirus disease 2019 (COVID-19) pandemic has caused unprecedented disruption to the normal operation of the healthcare system. On a worldwide scale, hospitals suspended nonurgent surgeries and outpatient visits to downsize clinical loadings to redistribute manpower to counteract the pandemic's impact. So far, there is no evidence-based guideline defining a clear line between urgent and nonurgent indications of intravitreal injections (IVI). Herein, we aimed to summarize IVI algorithm modifications and discuss the patient prioritization according to medical needs in the hostile environment in the COVID crisis. Assessing current literature, we found that neovascular age-related macular degeneration is considered the utmost priority among conditions that require IVI. Other conditions assigned with a high priority include monocular or quasi-monocular patients (only one eye > 20/40), neovascular glaucoma, and new patients with significant vision loss. Although patients with central retinal vein occlusion and proliferative diabetic retinopathy are not advised to delay treatments, we found no consistent evidence that correlated with a worse outcome. Diabetic macular edema and branch retinal vein occlusion patients undertaking treatment delay should be regularly followed up every 2 to 3 months. Serving as the principle of management behind the algorithm modifications, the reduction of both patient visit and IVI therapy counts should be reckoned together with the risk of permanent visual loss and COVID infection.